“Keep on rolling”: circulating cells in a botryllid ascidian torpor - Hyams, Yosef; Panov, Julia; Taranenko, Elizaveta; Brodsky, Leonid; Rinkevich, Yuval; Rinkevich, Baruch (Frontiers in Ecology and Evolution, 2023)
Hemocytes of the colonial tunicate Botrylloides leachii play important roles throughout the animal’s life span, including transport and storage of nutrients, respiration, regeneration, budding, sexual reproduction, defense responses, and tunic generation. Nevertheless, very little is known about the involvement of hemocytes or their functions in the remarkable torpor phenomenon characteristic of this species. Changes in water temperature result in rapid and dramatic morphological changes in which the entire colony degenerates, leaving remnants devoid of feeding and reproductive organs that form compacted and opaque masses of lacunae filled with hemocyte cells. Here, we study hemocyte populations in active and hibernating colonies at the morphological, cellular, and molecular levels using histological and transmission electron microscopy observations, primary cell culture observations, and single-cell transcriptomics. This study defines and captures the different cell types in torpor and control stages and further highlights torpor-associated cell types. Multinucleated cells (MNCs) appear only in torpor stages and under in vitro conditions and are most likely formed from cell fusions. Bacteria-carrying phagocytes are cells specific to a torpor state with yet unknown function. Single-cell sequencing analysis revealed 14 transcriptionally distinct cell clusters. The hibernating colonies had a low throughput of cells, yet all but two transcriptional clusters were present in hibernating colonies. A comparison of gene expressions in the same cell clusters revealed torpor-specific transcriptional modalities in seven of the cell types. Single-cell sequencing generates an enormous amount of valuable data that can serve researchers in future studies of ascidians and torpor phenomena and provide opportunities for future meta-analysis studies. However, the technical challenges create bottlenecks for the full exploitation of single-cell RNA sequencing (scRNA-seq) data. We developed an interactive, searchable, and intuitive cloud-based database where researchers can easily explore the single-cell transcriptomics data generated by us from active and torpid B. leachii colonies. The data can be interrogated and downloaded for further analysis and comparative studies. The Dashboard is available at: http://bleachii.tauberbioinformatics.org/seurat?id=Bleachii-v1. By elucidating hemocyte populations during hibernation, these results provide the basis for future studies of hibernation at the cellular and molecular levels in B. leachii and comparative studies of hibernation phenomena in other organisms.